An Analysis of Pharmacy Policy Implementation in Bantul Regency, Indonesia - Dhesi Ari Astuti; Hendy Ristiono; Evilia Nur Safitri (Journal of Public Health Sciences, 2022)
The Bantul Regency Government has arranged the implementation of pharmacy services so that a good business environment is established. This study was conducted to conduct a conceptual analysis of the establishment of pharmacies between high ratio and low ratio areas based on applicable regulations. The purpose of this study is to develop a policy of improving the effectiveness of drug supervision in pharmaceutical service facilities, and the formulation of patterns of strengthening and empowerment pharmacies. The method used is literature review on related articles from various countries. With certain filtering techniques, there are six articles meet the criteria. The results of the analysis of the article can be used to explain various patterns in the management of pharmacies implementation policies. The government needs to coordinate with associations, pharmacies provider on making policy that protect consumers. This policy is important because drug services have a broad impact on public health.